Karakteristik Jamur Makrokopis Di Hutan Lindung Kota Langsa - Anjani, Diyah; Alfisyahrin, Aura; Parsela, Jeli; Indriaty, Indriaty (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This study was motivated by the essential ecological role of macroscopic fungi in maintaining forest ecosystem balance and the lack of biodiversity data in the Protected Forest of Langsa City. The aim of this research was to identify and describe the morphological characteristics of macroscopic fungi and to assess their species diversity as a basis for scientific information. An exploratory survey method was used with direct field observation; sampling was conducted by exploring the forest area, and fungal identification was based on morphological characteristics such as cap shape, color, surface texture, lamella structure, attachment of the fruiting body, and habitat. The results showed that 15 species of macroscopic fungi were found, including Pycnoporus sanguineus, Ganoderma applanatum, Microporus xanthopus, and others, which were found growing on various substrates such as dead wood, soil, and animal dung. The observed cap shapes ranged from semicircular, fan-shaped, and umbrella-like to irregular oval, with diverse colors and textures. These findings indicate a high potential for fungal biodiversity in the area. This research provides essential baseline data to support conservation efforts and can be utilized for further exploration in pharmaceutical, food, and environmental education fields sustainably.